Evaluation of a physical activity promotion intervention for adults with whiplash associated disorders: a single-case experimental design study. Issue 23 (6th November 2022) - Ritchie, Carrie; Clanchy, Kelly; Sterling, Michele; Tate, Robyn; Smits, Esther J.; Day, Melissa; Nikles, Jane; Liimatainen, Jenna; Tweedy, Sean M.
Abstract: Purpose: There is considerable variation in the physical and psychological presentations of people with whiplash-associated disorder (WAD). Optimal treatment continues to be a challenge. This research evaluated the efficacy of a community-located, theory-based intervention designed to promote physically active behaviour in people with persistent WAD, and thereby improve perceptions of pain interference and confidence completing activities in the presence of neck pain. Materials and methods: A multiple-baseline, single-case experimental design was used to evaluate the 16-week intervention across six participants. Results: Weighted Tau- U showed significantly increased accelerometer-measured physical activity in three participants with large effect sizes (>0.5), with increased confidence in one participant (ES > 0.5), and reduced pain interference in another participant (ES > 0.7). Changes in other behaviours included clinically important improvements in quality of life for five participants and, in those participants with baseline symptom levels outside threshold levels, improvements in pain catastrophizing and pain self-efficacy. Conclusions: Participation in a theory-based intervention resulted in significant improvements in physical and psychological health for five of six participants. Providing this type of community-located physical activity promotion strategy, to individuals with persistent WAD, may help address physical impairments and psychological distress commonly experienced in WAD. Trial registration: The trial was registered with the Australia and New Zealand Clinical Trials Registry (ACTRN: ACTRN12617001261303p) and ClinicalTrials.gov (Protocol Number: 2018000349/2017/743). Implications for rehabilitation: Rehabilitation professionals should consider recommending theory-based physical activity promotion strategies to reduce physical impairments and psychological distress in individuals with persistent WAD. Individually tailored physical activity promotion strategies may help individuals with persistent WAD become more physically active thereby reducing their risk of diseases associated with inactivity which may compound the effects of WAD Improvements in physical and psychological health may occur independently of increasing habitual physical activity. Rehabilitation professionals may find that other community-located strategies which aim to promote physically active behaviour confer similar benefits for individuals with persistent WAD.